1992
DOI: 10.2307/1591757
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mice in the Epizootiology of Salmonella enteritidis Infection on Chicken Layer Farms

Abstract: A microbiological survey of 10 mice-infested poultry farms was conducted to determine the role of mice in the epizootiology of S. enteritidis infection. Five of the farms were rated as clean of S. enteritidis and five as contaminated based on culture results of environmental samples for S. enteritidis. Of 2103 environmental samples and 715 mice and rats tested, 5.1% and 16.2%, respectively, were culture-positive for S. enteritidis. On contaminated farms, S. enteritidis was isolated from 24.0% of the mice and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(142 citation statements)
references
References 12 publications
8
131
1
1
Order By: Relevance
“…24 At last, other risk factors which were not considered in the present study are important to 1 mention. For example, it could be useful to build a model taking into account flock 2 characteristics (type of breed, number of flocks on the farm, multi-age farm or not), farm 3 management (control of pest access, visitors allowed or not, feed composition and feeding 4 practices, drinking water), cleaning and disinfecting practices related with the contamination 5 status of the previous flock in the same hen house ( ( Henzler & Opitz, 1992;Kinde et al, 6 1996;Shirota et al, 2000;Garber et al, 2003;Liebana et al, 2003;Kinde et al, 2005). 7…”
Section: Discussionmentioning
confidence: 99%
“…24 At last, other risk factors which were not considered in the present study are important to 1 mention. For example, it could be useful to build a model taking into account flock 2 characteristics (type of breed, number of flocks on the farm, multi-age farm or not), farm 3 management (control of pest access, visitors allowed or not, feed composition and feeding 4 practices, drinking water), cleaning and disinfecting practices related with the contamination 5 status of the previous flock in the same hen house ( ( Henzler & Opitz, 1992;Kinde et al, 6 1996;Shirota et al, 2000;Garber et al, 2003;Liebana et al, 2003;Kinde et al, 2005). 7…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that S. Enteritidis was introduced into poultry flocks by rodents where it is endemic since in the distant past it was used as a rodenticide [51,71]. S. Enteritidis was first used to control rodent populations during the Yersinia pestis outbreak in San Francisco in 1895 and then occasionally in Europe until 1960 [127].…”
Section: Rodent Reservoirmentioning
confidence: 99%
“…The important role of mice in the dissemination and persistence of S. Enteritidis on poultry farms has been described in the past [5]. Recently, definitive molecular evidence for the involvement of several wildlife species in the maintenance of S. Enteritidis infection in layer farms was demonstrated [10].…”
Section: Enteritidis Contamination In the Fieldmentioning
confidence: 99%
“…A major factor in this increase has been attributed to consumption of undercooked eggs and egg products such as liquid egg, contaminated with S. Enteritidis [4]. Rodents, dirty environment, recent poultry farming practices, chicks, pullets, and feeds have all been considered as major sources for contamination with S. Enteritidis in chicken layer farms [5,7,[17][18][19]. In Japan, liquid egg is commonly used in making egg custard products.…”
mentioning
confidence: 99%